TIPE DAN STRUKTUR INFORMASI KALIMAT PASIF BAHASA INGGRIS PADA NOVEL DESECRATION - I Wayan Swandana (SPHOTA: Jurnal Linguistik dan Sastra, 2017)
ABSTRACT This research is entitled The Types and Information Structure of English Passive Sentence on the Novel Desecration. Basically active and passive sentences convey the same information with different syntactic and semantic structure. However, they have different focused meaning. It mainly aims at finding out: (1) the types and structure of passive sentence, and (2) the focused information in the passive sentence. Qualitative approach was used in this research and the data source was the novel entitled Desecration. The method used in collecting data was by using observation method followed by note taking technique. Intralingual comparison was used to analyze the classified data. The result of the analysis was presented by using formal and informal method. It was found that there were some types of passive sentence: (1) based on the agent, there are long and short passive, and (2) based on the predicator, there are: monotransitive, bitransitive, bare, and adjectival passive. Each type of these passive sentences has different structure. Based on the information structure, the passive sentence has structure as (1) focus – topic, and (2) focus only. The writer was aware that this research has some limitation or shortage so it is hoped that this research could be continued in order that it gets better result for the society in general. Key words: active sentence, focus, information structure, passive sentence, topic.